Diversity of non-marine gastropods of the Fiocruz Atlantic Forest Biological Station and adjacents urban areas, Rio de Janeiro, RJ, Brasil - FLAVIA C.S. RANGEL; SUZETE R. GOMES; THAMIRES CANUTO; PAULO S. RODRIGUES; SILVANA C. THIENGO (Anais da Academia Brasileira de Ciências, 2021)
Abstract Our main objective was to perform a preliminary survey of the non-marine gastropods at the Estação Biológica Fiocruz Mata Atlântica (EFMA) and its adjacent urban areas, also considering samples from other localities of the Parque Estadual da Pedra Branca received as donation, in Rio de Janeiro, RJ, Brazil. Infection by larval helminths of medical and veterinary importance was also investigated in 348 specimens of five freshwater species and two specimens of the terrestrial species Achatina fulica. In all, 584 samples of molluscs from 34 collection sites were obtained. They represented 31 species classified in 16 families. Fifteen species were exclusive to the EFMA area. In the urban area mainly exotic and/or synanthropic species were found. Some of them were found in the forest border as well. The freshwater Biomphalaria tenagophila, an intermediate host of the trematode that causes schistosomiasis mansoni, was found parasitized by Xiphidiocercarie cercariae and the Afro-asiatic Melanoides tuberculata by Pleurolophocercus cercaria. The finding of endemic and exotic species, including transmitters of parasites, demonstrate the importance of fast surveys such as the present study. However, considering the great diversity of endemic molluscs found in a relatively small part of the EFMA, we highlight the necessity of further additional studies.